2021
DOI: 10.3389/fpubh.2021.657082
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors on Health Information to Improve Public Health Literacy in the Official WeChat Account of Guangzhou CDC

Abstract: Background: Social media is used as a new channel for health information. In China, the official WeChat account is becoming the most popular platform for health information dissemination, which has created a good opportunity for the Centers for Disease Control and Prevention to facilitate health information online to improve emergency public health literacy.Methods: Data were collected from the Guangzhou CDC i-Health official WeChat account between April 1, 2018 and April 30, 2019. Descriptive analysis was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…Social media brings a new dimension to health care with the possibility of potentially improving health outcomes [ 20 ]. As a new channel for health information, social media accounts could be an effective, sustainable, and feasible strategy [ 21 ]. With an ever-growing telecommunications industry, mobile technology is increasingly used for health education and assistance in behavior change around the globe for health care practice [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Social media brings a new dimension to health care with the possibility of potentially improving health outcomes [ 20 ]. As a new channel for health information, social media accounts could be an effective, sustainable, and feasible strategy [ 21 ]. With an ever-growing telecommunications industry, mobile technology is increasingly used for health education and assistance in behavior change around the globe for health care practice [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Attractive titles can engage more of the public [ 40 ] and our results also suggest the importance of an exclamation/emphasis title. We reported that titles containing obvious COVID-19-related words had a negative impact on users’ information behavior in terms of re-sharing an article during the COVID-19 outbreak, which was inconsistent with reports from the Guangzhou CDC [ 21 ]. This might be due to most articles during the outbreak being related to the COVID-19 pandemic and COVID-19-related titles not generating public attention.…”
Section: Discussionmentioning
confidence: 62%
“…Researchers have identified factors relating to government agency’ use of social media and public engagement during a public health emergency, but mainly involving Facebook and Twitter (which are frequently used abroad [ 20 ]), specific single accounts [ 21 ], or changes in number and content of articles [ 17 , 22 ]. Additionally, the primary period for data acquisition focused on the early stage of the COVID-19 pandemic [ 16 , 23 ].…”
mentioning
confidence: 99%
“…Continuous variables included the number of images in article, the number of words in article, user engagement of followers 7 days after the article was published, previous studies used one or combination of “views”, shares, and “likes” or add to favorites as measurement of user engagement [ 16 – 19 , 20 , 21 ], researches indicated that sharing an article shows users’ interest in a certain health theme [ 22 ]. Liking a post reflects their preference and appreciation [ 19 , 23 ].…”
Section: Methodsmentioning
confidence: 99%